2017
DOI: 10.1097/md.0000000000007304
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HPV distribution in patients with cervical precancerous lesions in Western China

Abstract: Cervical human papillomavirus (HPV) infection is a dangerous disease, whose subtypes exhibit different distribution patterns in particular countries, regions, and races. In this study, the HPV distribution in patients with cervical precancerous lesions in Western China was investigated to assess a probability for prevention of cervical cancer and the clinical application of an HPV vaccine in China. The retrospective study of patients with different HPV subtypes and cervical precancerous lesions, who have under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 18 publications
(11 reference statements)
3
24
1
Order By: Relevance
“…The cervical HPV infection rate in patients with cervical lesions is significantly higher than that of the general population and is significantly region‐related . The present study systematically analyzed the high‐risk HPV infections in patients with cervical intraepithelial neoplasia and cervical cancer in different regions of mainland China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cervical HPV infection rate in patients with cervical lesions is significantly higher than that of the general population and is significantly region‐related . The present study systematically analyzed the high‐risk HPV infections in patients with cervical intraepithelial neoplasia and cervical cancer in different regions of mainland China.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent infection with high‐risk human papillomavirus (HPV) is the primary cause of cervical cancer. Our group analyzed HPV infections in patients with cervical cancer or precancerous cervical lesions and found that 90.8% of cervical cancer patients were infected with high‐risk HPVs, and the 5 subtypes of high‐risk HPV with the highest infection rate were 16, 18, 58, 53, and 33; 76.6% of patients with precancerous cervical lesions were infected with high‐risk HPVs, and the top 5 infectious subtypes were 16, 52, 58, 33, and 18 . Studies have shown that HPV subtypes have significant age and regional specificities, which differed in different levels of precancerous cervical lesions and cervical cancer .…”
mentioning
confidence: 99%
“…(4) The total case number of each category and HR-HPV infection. 15 types of HR-HPV types were collected, namely, HPV 16,18,31,33,35,39,45,51,52,56,58,59,68,73,82, and other probable high-risk types (e.g., HPV 53, 66, and83). (5) Area: Given the geographical distribution, the areas involved in this study are divided into East China (i.e., Shanghai, Jiangsu, Zhejiang, Anhui, Jiangxi, Shandong, Fujian, and Taiwan province), North China (i.e., Beijing, Tianjin, Shanxi, Hebei, and Central Inner Mongolia Autonomous Region), Central China (i.e., Henan, Hubei, and Hunan province), South China (i.e., Guangdong, Guangxi Zhuang Autonomous Region, Hainan province, the Hong Kong Special Administrative Region, and Macao Special Administrative Region), Southwest China (i.e., Chongqing, Sichuan, Guizhou, Yunnan Province, and the Tibet Autonomous Region), Northwest China (i.e., Shanxi, Gansu, Qinghai, Ningxia Hui Autonomous Region, Xinjiang Uygur Autonomous Region, Inner Mongolia Autonomous Region, and West La Shan Au), and Northeast China (i.e., Heilongjiang, Jilin, Liaoning, and East of Inner Mongolia).…”
Section: Data Excerptmentioning
confidence: 99%
“…Articles for Northeast China, North China, East China, South China, Central China, Northwest China, Southwest Chinawere obtained. A total of eight HR-HPV genotypes (i.e., HPV 16,18,31,33,52,58,59, and 68) of cervical cancer were selected by synthetically analyzing the top five high-risk types of cervical cancer in different regions. Figure 3).…”
Section: Meta-analysis Of the Top Five High-risk Types Of Cervical Camentioning
confidence: 99%
See 1 more Smart Citation